2023
DOI: 10.1111/nph.19284
|View full text |Cite
|
Sign up to set email alerts
|

GH3‐mediated auxin inactivation attenuates multiple stages of lateral root development

Qing Wang,
Hugues De Gernier,
Xingliang Duan
et al.

Abstract: Summary Lateral root (LR) positioning and development rely on the dynamic interplay between auxin production, transport but also inactivation. Nonetheless, how the latter affects LR organogenesis remains largely uninvestigated. Here, we systematically analyze the impact of the major auxin inactivation pathway defined by GRETCHEN HAGEN3‐type (GH3) auxin conjugating enzymes and DIOXYGENASE FOR AUXIN OXIDATION1 (DAO1) in all stages of LR development using reporters, genetics and inhibitors in Arabidopsis thaliana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This observation supports the notion of elevated auxin levels facilitating root growth in transgenic plants as compared to their wildtype counterparts under saline conditions (data not shown). Previous studies in Arabidopsis showed that GH3 protein act as a negative regulator in lateral root development and promoting primary root growth (Wang et al, 2023). Auxin-responsive GH3-like protein 5 under salinity stress, and both Indole-3-acetic acid-amido synthetase GH3.10 and GH3.11 under drought conditions were increased in transgenic plants supporting significantly higher primary root length in transgenic plant seedling (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This observation supports the notion of elevated auxin levels facilitating root growth in transgenic plants as compared to their wildtype counterparts under saline conditions (data not shown). Previous studies in Arabidopsis showed that GH3 protein act as a negative regulator in lateral root development and promoting primary root growth (Wang et al, 2023). Auxin-responsive GH3-like protein 5 under salinity stress, and both Indole-3-acetic acid-amido synthetase GH3.10 and GH3.11 under drought conditions were increased in transgenic plants supporting significantly higher primary root length in transgenic plant seedling (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced expression of OsYUCC5 confirmed local auxin biosynthesis in buds, which is necessary as an auxin source. The GRETCHEN HAGEN 3 (GH3) acyl acid amido synthetase family, pivotal in conjugating IAA with amino acids, has been proposed as part of an important auxin attenuation mechanism, based on its auxin-conjugating enzymatic activity and gain-of-function phenotypes [ 33 , 34 ]. Here, we found that the relative expressions of OsGH3.8 and OsGH3.6 in the axillary bud outgrowth were significantly induced after GR24 treatment ( Figure 6 A), which implies that SL may affect the IAA content in ratoon rice by promoting IAA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the exogenous addition of IAA-aa and IAA both rapidly increased content-free IAA levels and exhibited similar high growth factor phenotypes, suggesting that IAA-aa is a storage form of IAA [ 103 ]. Subsequent studies found that these IAA-aa, IAA-Leu, and IAA-Ala could be reversibly converted to free IAA by the action of the hydrolases, IAA-LEUCINE RESIS TANT1 (ILR1), ILR1-LIKE proteins (ILLs), and IAA-ALANINE RESISTANT3 (IAR3) [ 5 , 104 , 105 ].…”
Section: Atypical Roles Of Group II Gh3 and Iaa-amino Acidsmentioning
confidence: 99%